Analysis of the Effectiveness of the Digital Role on Manual Archive Management at the Binjai Branch Office of BPJS Employment - Miftahul Husna Hutapea; Wahyu Syarvina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Archives are several important information documents that are collected so that they can be stored in a planned and orderly manner in a good and safe manner so that when one day in the future these documents can be found when needed. Based on the Decree of the President of the Republic of Indonesia Number 105 of 2004 regarding archive management, chapter I Article 1 explains that archives are defined as a collection of manuscripts made and accepted by Government Agencies and Private Agencies or individuals, in any form individually or in groups. in the context of implementing government activities as well as in the context of implementing national life. The archive data files will increase day by day, so that the data files can be neatly arranged, a proper management system is needed. So that it can be seen that the purpose of this study is to find out the advantages and disadvantages of implementing an archive management system both digitally and manually. So that it can show which system is more efficient to implement in managing archives at the BPJS Ketenagakerjaan office, Binjai Branch. As well as benefits The results of this study are expected to be used as input and information to be used as a reference in order to improve the performance of archive management in the work unit.